2020
DOI: 10.1038/s41598-020-66822-z
|View full text |Cite
|
Sign up to set email alerts
|

The bovine cumulus proteome is influenced by maturation condition and maturational competence of the oocyte

Abstract: In vitro maturation (IVM) of oocytes has still a negative impact on the developmental competence of oocytes. Therefore, this study analysed the cumulus proteome of individual cumulus-oocyte complexes (COCs) with and without maturational competence, matured under in vivo or in vitro conditions (n = 5 per group). A novel, ultrasensitive mass spectrometry (MS) based protein profiling approach, using label-free quantification, was applied. The detected cumulus proteome included 2226 quantifiable proteins and was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 82 publications
(101 reference statements)
0
30
0
1
Order By: Relevance
“…Nonetheless, the few studies described many proteins involved in cell signaling that may have a role in cumulus-oocyte communication and competence. Most of the proteins are involved in components of integrin, actin cytoskeleton, mitogen-activated protein kinases (MAPK) and phosphatidylinositol 3-kinase (PI3K) signaling pathways, extracellular matrix (ECM) receptor interactions, steroid biosynthesis, and glucose and carbohydrate metabolism, which may have implications in various reproductive processes such as oocyte development and maturation [156][157][158] (Table 2). A recent study reported a highly sensitive approach to characterize the CC proteome from a single COC after in vivo or in vitro maturation [156].…”
Section: Transcriptomic and Proteomic Of Cumulus Cellsmentioning
confidence: 99%
“…Nonetheless, the few studies described many proteins involved in cell signaling that may have a role in cumulus-oocyte communication and competence. Most of the proteins are involved in components of integrin, actin cytoskeleton, mitogen-activated protein kinases (MAPK) and phosphatidylinositol 3-kinase (PI3K) signaling pathways, extracellular matrix (ECM) receptor interactions, steroid biosynthesis, and glucose and carbohydrate metabolism, which may have implications in various reproductive processes such as oocyte development and maturation [156][157][158] (Table 2). A recent study reported a highly sensitive approach to characterize the CC proteome from a single COC after in vivo or in vitro maturation [156].…”
Section: Transcriptomic and Proteomic Of Cumulus Cellsmentioning
confidence: 99%
“…The findings of the present study enhance our knowledge of bovine ffEV protein cargo. Indeed, until now, EV-proteomic studies in bovine have been limited to exosomes derived from milk ( 44 ) plasma, saliva, urine ( 27 , 28 ), oviduct fluid ( 10 ), and spent medium containing ovarian cell secretions ( 45 ). Here, we identified 322 proteins in ffEVs.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic of ffEVs makes them a valuable source of novel diagnostic and therapeutic strategies in reproductive medicine ( 74 ). Although their utility is theoretical currently, data have shown that levels of cumulus proteins were different in mature and non-mature COCs ( 45 ). These differential proteins were detected in ffEVs, and therefore, ffEVs may be involved in the acquisition of competence by the enclosed oocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the few studies have described many proteins involved in the cell signaling that may have a role in cumulus-oocyte communication and competence. Most of the proteins involved are components of integrin, actin cytoskeleton, MAPK and PI3K signaling pathways, ECM-receptor interactions, steroid biosynthesis, glucose and carbohydrate metabolism, that may have implications in various reproductive processes such as oocyte development, and maturation [154,155] (Table 2). A recent study reports a highly sensitive approach to characterize the CC proteome from a single COC after in vivo or in vitro maturation [154].…”
Section: Transcriptomic and Proteomic Of Cumulus Cellsmentioning
confidence: 99%
“…Most of the proteins involved are components of integrin, actin cytoskeleton, MAPK and PI3K signaling pathways, ECM-receptor interactions, steroid biosynthesis, glucose and carbohydrate metabolism, that may have implications in various reproductive processes such as oocyte development, and maturation [154,155] (Table 2). A recent study reports a highly sensitive approach to characterize the CC proteome from a single COC after in vivo or in vitro maturation [154]. This method shows the potential to directly connect the cumulus proteome to the developmental potential of the corresponding oocyte, as already performed at gene expression level.…”
Section: Transcriptomic and Proteomic Of Cumulus Cellsmentioning
confidence: 99%